2022
DOI: 10.3390/biomedicines10071490
|View full text |Cite
|
Sign up to set email alerts
|

P63 and P73 Activation in Cancers with p53 Mutation

Abstract: The members of the p53 family comprise p53, p63, and p73, and full-length isoforms of the p53 family have a tumor suppressor function. However, p53, but not p63 or p73, has a high mutation rate in cancers causing it to lose its tumor suppressor function. The top and second-most prevalent p53 mutations are missense and nonsense mutations, respectively. In this review, we discuss possible drug therapies for nonsense mutation and a missense mutation in p53. p63 and p73 activators may be able to replace mutant p53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 162 publications
0
10
0
Order By: Relevance
“…ΔNp63 is the predominant p63 isoform, which is vital for tumorigenesis and progression and senescence suppression and is associated with poor OS in HNC. [120][121][122] P63 is considered a stem cell marker. 123 Moreover, ΔNp63 affects the growth factor signaling pathway and tumor metabolic microenvironment through hyaluronic acid signaling and a transcriptional program.…”
Section: Mapk Pathwaymentioning
confidence: 99%
“…ΔNp63 is the predominant p63 isoform, which is vital for tumorigenesis and progression and senescence suppression and is associated with poor OS in HNC. [120][121][122] P63 is considered a stem cell marker. 123 Moreover, ΔNp63 affects the growth factor signaling pathway and tumor metabolic microenvironment through hyaluronic acid signaling and a transcriptional program.…”
Section: Mapk Pathwaymentioning
confidence: 99%
“…Either in concert with or as a substitution for p53, p63 and p73 tightly regulate proliferation, metabolic activity, cell differentiation and initiation of apoptosis and/or ferroptosis [ 51 , 53 , 54 , 55 , 56 ]. However, p63 and p73 have a lower mutational rate than p53 [ 57 ].…”
Section: Somatic Mutations In Hcc Pathogenesismentioning
confidence: 99%
“…Indeed, the Vousden and Muller teams demonstrated that mutants p53 can induce a loss of directionality of migration, promote invasion, and interfere with the metastatic behavior [ 30 , 31 ]. The functions of p63 and p73 in the cancer context have been deeply studied [ 8 , 27 , 32 , 33 ]. Regarding p73, several knockdown (KD) in vivo experiments were done to evaluate the role of both TAp73 and ΔNp73 isoforms.…”
Section: P53 Protein Family In Primary Tumors and Metastatic Dissemin...mentioning
confidence: 99%